GE_GERICHTE C/550/2016 vom 24. Mai 2017 - GE Cour de justice (2017)
FAILLITE SANS POURSUITE PRÉALABLE ; INSOLVABILITÉ ; CONFISCATION(DROIT PÉNAL) ; CONSEIL FÉDÉRAL ; ORDONNANCE | LP.174.2; LP.190.1.2; OUkraine.1.1;